2020
DOI: 10.1136/bmjopen-2019-032652
|View full text |Cite
|
Sign up to set email alerts
|

Integrated care experiences and out-of-pocket expenditures: a cross-sectional survey of adults receiving treatment for HIV and hypertension in Malawi

Abstract: ObjectivesAs HIV-positive individuals’ life expectancy extends, there is an urgent need to manage other chronic conditions during HIV care. We assessed the care-seeking experiences and costs of adults receiving treatment for both HIV and hypertension in Malawi.Design, setting and participantsA cross-sectional survey was conducted with HIV-positive adults with hypertension at a health facility in Lilongwe that offers free HIV care and free hypertension screening, with antihypertensives available for purchase (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…A majority of the studies (n=7) had their origin/geographical focus in South Africa (SA). One study was conducted in Kenya, 22 Tanzania, 31 Uganda, 30 Malawi, 29 Northern Thailand 27 and North Carolina (USA), respectively 28 ( table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A majority of the studies (n=7) had their origin/geographical focus in South Africa (SA). One study was conducted in Kenya, 22 Tanzania, 31 Uganda, 30 Malawi, 29 Northern Thailand 27 and North Carolina (USA), respectively 28 ( table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…► A desire for an integrated care model where all their care was consolidated in one place, with one provider. ► Positive towards increased participation from HIV clinic support staff Moucheraud et al 29 Fragmented and integrated care Fragmented (non-integrated care) ► Additional costs (ie, beyond costs already incurred for ART visits), costs of transportation to refill visits and lost wages during refill visits. ► Refill location for medicines chosen primarily due to perceived lower medication costs and proximity/convenience (eg, distance to home).…”
Section: Continuity Of Care and Appointment Systemsmentioning
confidence: 99%
“…A pilot study in Tanzania and Uganda found that managing two or more conditions in a single participant was cheaper (for both the health system and the patient) than managing multiple conditions separately [62]. A study in Malawi similarly found lower out-of-pocket costs for patients in integrated care, compared to non-integrated care [63]. Intersectoral financing and/or community-based micro-financing to address both multiple determinants of health are also being explored as options to support the scale-up of integrated care [64,65].…”
Section: Integrated Service Deliverymentioning
confidence: 99%
“…While patients can travel to a government clinic to obtain free medications, the additional time (including time away from work, childcare, or other responsibilities) and cost of transport may serve as a significant barrier to obtaining refills elsewhere. Previous research by our group showed that despite the costs of medications, integrated care in which medications for hypertension are purchased at the point of care does provide cost savings for people living with HIV due to the efficiencies created by avoiding the time and opportunity costs of seeking free medications elsewhere [ 24 ]. Real world and cost-modeling data have also shown that integrated care reduces costs from the health system perspective [ 25 26 ], and additional cost modeling work will be important to help inform policy around the implementation of NCD care for people with and without HIV.…”
Section: Discussionmentioning
confidence: 99%